2012
DOI: 10.2527/jas.2011-4434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum CJLP243 on the growth performance and cytokine response of weaning pigs challenged with enterotoxigenic Escherichia coli1

Abstract: The purpose of the present study was to evaluate the effect of diets containing Lactobacillus plantarum CJLP243 on the growth and cytokine response of weaning pigs (Sus scrofa) challenged with enterotoxigenic Escherichia coli (ETEC). In a 28-d experiment (14 d before and 14 d after challenge), a total of 108 pigs at 20 ± 1 d of age were allotted to 1 of 6 diets. These were a control diet without ETEC challenge (CON) and 5 treatment diets with ETEC challenge, including a control diet with ETEC challenge (negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
5
50
0
Order By: Relevance
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
“…probiotics are related to their competitive exclusion of pathogenic bacteria (Lee et al 2012). The way in which Lactobacillus species inhibit pathogens growth has been attributed to steric hindrance of binding sites (Ouwehand and Conway 1996), pH values (Lehto and Salminen 1997) and certain components of the lysed cell wall (Lehto and Salminen 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, probiotic cultures need to have the following characteristics in order to exert a positive effect on pig performance: (1) the ability to colonize the gastrointestinal tract (GIT), (2) high growth rate and a low requirement for nutrients, (3) suppress enteric pathogens, either its cells or metabolites, (4) grown easily on a large scale under commercial conditions; and (5) survive in infeed and from the manufacturing process with a stable activity (de Lange et al 2010). Many available data support Lactobacillus, as being probiotics that have positive effects on the growth performance of piglets (Huang et al 2004;Wang et al 2009;Lee et al 2012;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that weaned piglets experienced diarrhoea and poor growth performance when orally challenged with the enterotoxigenic Escherichia coli (ETEC) strain within a short period following weaning (Liu et al, 2013;Bontempo et al, 2014). Lee et al (2012) also observed reduced growth performance and diminished faecal consistency, as well as increased inflammatory response, in piglets challenged by ETEC within 14 days following weaning (Lessard et al, 2009). In this study, the injections of E. coli on days 21 and 25 reduced the gain-to-feed ratio during the three weeks post-challenge, which may indicate that E. coli challenge (double inoculations in older piglets) can induce negative effects on piglets' growth performance even after their gut microbial environment has matured.…”
Section: Discussionmentioning
confidence: 99%